Misinterpretation of Frozen Section in Endometrial Cancer Cases: Does It Have Any Effect on Disease-free and Overall Survival?. (November 2017) - Şenol, Taylan; Polat, Mesut; Özkaya, Enis; Karateke, Ateş
Abstract : The aim of this study was to assess whether misinterpretation of frozen sections in endometrial cancer cases is associated with survival and determine the factors leading to mismatch. One hundred fifty endometrial cancer cases treated in Zeynep Kamil Maternity and Children's Health Training and Research Hospital between January 2010 and December 2014 were included in the study. Frozen sections and final histopathologic reports were screened from a prospectively collected database and analyzed on whether mismatch between the initial and the final reports has any impact on disease-free survival. There were 31 patients with mismatched frozen sections with the final report, whereas in 119 patients, frozen sections and final reports were consistent. The recurrence-free survival time was similar between groups (51 vs. 49, P =0.813). Overall survivals were also similar between groups (55 vs. 52, P =0.880). Frozen section misinterpretation does not affect disease-free and overall survival in endometrial cancer cases.